Variação cronobiológica de fatores imunológicos, bioquímicos e hemorreológicos de pacientes diabéticos hemodialisados - Lima, Fernando Almeida (2019)
Diabetes mellitus is a chronic disease characterized by hyperglycemia, among the main consequences are CKD and cardiovascular problems. It is currently one of the main causes of chronic renal failure, leading patients with diabetic nephropathy to renal replacement therapy programs, leading to immunological, biochemical and hematological changes. Chronobiological variations of cytokines and some hormones can be observed in some chronic diseases according to the oscillations of the circadian rhythm of each individual. Objective: To evaluate the chronobiological profile of immunological, biochemical and hemorheological factors and to relate these parameters in patients with diabetic nephropathy in two different periods of hemodialysis. Methods: Blood samples were collected from 37 patients with type 2 diabetes mellitus in a regular state of hemodialysis divided into four groups involving the genders and the treatment period to evaluate the concentration of IL-2, IL-4, IL-6, IL- 10, IL-17, TNF-α and IFN-γ, biochemical and hemorheological parameters. For statistical analysis, the T-test for independent samples was used to compare mean analyzes, Pearson's correlation test and ANOVA in Bioestat 5.0 software, and the differences were considered significant with p <0.05. Results: After statistical analysis, IL-10 and TNF-α presented significant results, where they started to present changes in relation to chronobiology. Involving periods and gender, TNF-α was elevated in the morning for men, followed by an increase in IL-10 for women in the evening period. In the TNF-α correlation tests with the other cytokines, there was a positive correlation with IL-2 and IFN-γ in both HD periods, with an inflammatory profile, when relating period and gender, TNF-α showed no correlation the female group and only the male group with IFN-γ in both periods and IL-2 in the afternoon. For IL-10 correlations, there was positive regulation for both genders in the evening shift. Urea and creatinine values were higher in both periods for men. Hemorheological analyzes showed higher viscosity and lower deformation rate in the afternoon for women.Conclusion: Considering the results, this study corroborates the hypothesis that the morning period becomes more damaging to the male patients, since TNF-α was elevated at this stage and IL-10 seems to regulate the inflammatory response in the evening period for both genders in a positive way with proinflammatory cytokines (IL-2, TNF-α, IFN-γ and IL-17).